Judges 1-12 : a new translation with introduction and commentary (The Anchor Yale Bible, 2013)
" Informed by the cultures of the ancient world, this fresh translation and insightful commentary to chapters 1 to 12 of the biblical book of Judges provide a multilayered analysis of some of Scripture's most stirring narratives and verses. It expands understanding of the Hebrew text by explaining its meaning, exploring its contexts, and charting its effect over time. A comprehensive Introduction surveys issues and approaches in the study of Judges. Introductory Remarks identify issues of religious, social, cultural, or historical significance for most segments. These provide a background to the Notes and frame for the exposition in the concluding Comments"